STRATEGI SEGMENTING, TARGETING, POSITIONING SERTA STRATEGI HARGA PADA PERUSAHAAN KECAP BLEKOK DI CILACAP - Hari Wijaya; Hani Sirine (Asian Journal of Innovation and Entrepreneurship, 2016)
To win the market competition, companies must have segmenting, targeting, positioning strategy and pricing strategy. This study aims to determine segmenting, targeting, positioning strategy as well as the company's pricing strategies on Kecap Blekok Company in Cilacap. Methods of data collection in this study using interviews and documentation. The analysis technique used is descriptive analysis techniques. The results showed market segment of Kecap Blekok Company is the lower middle class, the chosen target market is segment concentration or a single market, Kecap Blekok Company is positioned on the lower middle class with high quality. For the pricing strategy is employed by Kecap Blekok Company using cost plus pricing method to set the selling price.